Formation of Methyl Pyrazine during Cocoa Bean Fermentation - Selamat, Jinap; Harun, Siti Mordingah; Mohd. Ghazali, Norsiati (Universiti Putra Malaysia Press, 1994)
A study on the effect of four fermentation techniques currently practised in Malaysia on the types and amount of pyrazines produced and the growth of Bacillus sp. in cocoa beans was carried out. Freshly harvested beans were fermented using wooden shallow (032m in depth), medium (0.61 m), deep (0. 9Om) boxes for 6 d and turned every 4B h for the shallow and medium fermentations, and every 24 h for the deep fermentation; beans that had undergone 10 d pod storage were also fermented in shallow box for 5 d and turned on 4Bth hour. Samples were determined for nib pH, titratable acidity, fermentation index and pyrazines. Number of Bacillus sp. bacteria were monitored and identified. The type and amount of pyrazines detected varied with the techniques employed. Pod-stored samples contained 2,3,5,6-tetramethylpyrazine (19. Bug/1OOg) and the highest concentration of 2,3,5-trimethylpyrazine (23.0ug/ 100g), 2,5-dimethylpyrazine (154. Bug/1 OOg) and total pyrazine (177. 6ug/1 OOg). Samples fermented in shallow and medium box fermentations contained 2,3,5-trimethylpyrazine and 2,5- dimethylpyrazines; those of the deep box contained only 2,5-dimethylpyrazine. Bacillus sp. increased along with 2,3-dimethylpyrazine, 2,3,5trimethylpyrazine and total pyrazine as fermentation Period increased, with a correlation (r2) of 0.90. The isolated Bacillus sp. were identifted as B. subtilis and B. megaterium. 2,5-dimethylpyrazine was present in all samples; the component could be common in cocoa fermented in Malaysia.